Impact of intra‐operative hypotension on mortality rates and post‐operative complications in dogs undergoing cholecystectomy. (26th August 2020) - Hattersley, R.; Downing, F.; Gibson, S.; Demetriou, J.; Elmenhorst, K.; Kulendra, N.; Mielke, B.; Woods, S.
Abstract : Objectives: To report the mortality rate within a cohort of dogs undergoing cholecystectomy and investigate the impact of intra‐operative hypotension on mortality. Materials and Methods: Clinical records at five UK referral centres were reviewed for dogs undergoing cholecystectomy. Data collected included presenting signs, pre‐operative blood test results, intra‐operative data including frequency and duration of hypotension and the incidence and type of post‐operative complications. Results: Data from 119 dogs were included. Sixteen dogs (13%) died before discharge and by 28 days after surgery the total mortality was 19 dogs (17%). Hypotension lasting over 10 minutes during general anaesthesia occurred in 65 dogs (54.6%), with a mean ± sd duration of 36.1 ± 30.0 minutes. Intra‐operative hypotension or the number of hypotensive episodes did not appear to be associated with in‐hospital or 28‐day mortality. American Society of Anaesthesiologists grade (of fitness for surgery) was significantly associated with both in‐hospital and 28‐day mortality on univariable analysis, as were post‐operative hypoproteinaemia, ileus and pancreatitis. However on multivariable analysis, only ileus and pancreatitis were found to significantly impact mortality. Clinical Significance: Dogs presenting with a higher American Society of Anaesthesiologists grade appear to have a higher risk of mortality, although intra‐operative hypotension did not appear to be part of this risk.